Torsion of Granulosa Cell Tumor of the Ovary in a Preschool Patient: A Rare Cause of Acute Abdomen - Siviero, Ivonete (Am J Case Rep, 2020)
Patient: Female, 5-year-old Final Diagnosis: Granulosa cell tumor of the ovary Symptoms: Abdomen distension • abdominal mass • abdominal pain Medication:— Clinical Procedure: Diagnostic tests, surgical treatment and chemotherapy Specialty: Pediatrics and Neonatology OBJECTIVE: Rare disease BACKGROUND: Granulosa cell tumor of the ovary is very rare in childhood; its most common clinical manifestation is isosexual precocious puberty. Clinical presentation as acute abdomen due to pain and ovarian torsion is rare, but a granulosa cell tumor must be suspected in a patient with this acute presentation and signs of early puberty. Adult-type granulosa cell tumor is an even rarer occurrence in children. CASE REPORT: We report a case of torsion of adult-type granulosa cell tumor of the ovary in a 5-year-old patient with acute abdominal pain and ovarian torsion and highlight the importance of histological diagnosis of this tumor for the therapeutic plan and progression of these patients. CONCLUSION: Precocious puberty, pain, abdominal distension, and an ultrasonography with suspicion of ovarian torsion are warning signs that may indicate the presence of a gonadal stromal tumor in pediatric patients seen at an emergency unit. These patients require long-term follow-up by a pediatrician and gynecologist because of the potential for late recurrence.